The Impact of Financial Literacy and Religious Knowledge of Traders on the Willingness to Engage in Sharia-Compliant Transactions - Pribadi, Firman syakri; Ardian, M; Safardi, Safardi; Patrianagara, Patrianagara (International Journal of Management and Digital Business, 2025)
This study seeks to assess the impact of financial literacy and religious knowledge on the propensity for sharia-compliant transactions among traders in Gandoriah Beach, Pariaman City. The sample consisted of 56 respondents. This research is quantitative. Data was acquired from primary sources and analyzed using multiple linear regression approaches, with processing conducted via SPSS Software Version 25. The data gathering approach employed a questionnaire, whilst the data analysis strategy utilized multiple linear regression analysis. The study's results indicated that financial literacy significantly influenced the propensity for Sharia-compliant transactions. The presence of financial literacy and religious awareness among traders will enhance the tendency for Sharia-compliant transactions in Gandoriah Beach, Pariaman City. Financial literacy and religious understanding concurrently exert a substantial influence on the propensity for engaging in Sharia-compliant activities